REPRESENTATION OF RELIGIOUS AND MORAL VALUES IN THE ENGLISH TEXTBOOK FOR INDONESIAN JUNIOR HIGH SCHOOL: A CDA INVESTIGATION - Nadhif, Ahmad (IAIN PONOROGO, 2017)
This research aims to examine the construction of the discourse of religious and moral values within the official English textbook for Indonesian high school students and to expose the underlying ideology. The textbook analyzed is the official English textbook for junior high school grade VII, Bahasa Inggris: When English Rings the Bell. This study makes use of Fairclough?s three dimensional models, namely textual, processing, and socio-cultural analysis. In the level of textual analysis, the researcher addresses the issues of transitivity and modality. In the processing stage, the focus is on the issue of assumption. Meanwhile, the ideology investigation is done in the last level. The findings shows that the discourse of the religious and moral values are classified into four main categories: values toward one?s self (e.g being disicpline regarding the time), values toward others (e.g loving them and being attentive to their occupation and physical appearance), values toward animals (i.e. loving and being attentive to them), and values toward things around (i.e. being attentive to them). The Critical Discourse Analysis (CDA) investigation reveals that the discourse of religious and moral values within this book represents some dominating ideologies, such as the western-secular way of greeting people, the outschool activites of the mid-high social class, the rich?s-style house furniture, and the notion that beauty is identical with white skin and straight hair, the capitalism-driven economics system, as well as the idea of woman emancipation by the feminist movement.